The Effect Of Examination Stress On Total Leucocyte Count Of Non-Obese And Obese Medical Students - Hassan, Hamid; Mujeeb, Bariqa; Ali, Liaqat; Noor, Fatima; Murtaza, Muhammad Ayhan (Journal of Rawalpindi Medical College, 2025)
Objective: To assess the degree of stress before, within and later to examination and to correlate it with Total Leukocyte Count (TLC), Body Mass Index (BMI) and waist-hip ratio (WHR) of participants. Materials and Methods: 92 individuals, randomly selected, were placed into non-obese male and female (NOMs and NOFs) and obese male and female (OMs and OFs) categories with 23 individuals in each group. The degree of stress was assessed before, within and later to a crucial examination spell via the Perceived Stress Scale (PSS) and TLC was also assessed at each of the occasions. To compare the differences between TLC and stress ANOVA in combination with Post Hoc Tukey’s Test was used while to correlate these with BMI and WHR Pearson’s correlation was applied. Results: Obese males experienced a much higher degree of stress as compared to age-matched NOMs (p=0.00). Also, obese males during heightened stress showed a significant dip in their TLC as compared to NOMs (p=0.01) and OF (p=0.00). Moreover, the PSS score showed a strong negative correlation with TLC in NOMs (r=-0.47, p=0.02), NOFs (r=-0.42, p=0.04), OMs (r=-0.73, p=0.00) and OFs (r=-0.41, p=0.04). Conclusion: Examination stress significantly affects the immune status of young adults with obese males experiencing much more immunosuppression as compared to age and ethnicity-matched obese females as well as non-obese males.